A French braggart in the Dutch republic: the architect Georges- Francois Blondel (Bulletin KNOB, 2008)
The architect Georges-Francois Blondel (1730-after 1792), son of the well-known architecture-theoretician J.F. Blondel, has always remained a somewhat shadowy figure, also because his life and career took place in several countries. In this article all the biographical information known about him so far has been compiled for the first time, largely on the basis of older literature.Initially, G.F. Blondel was educated by his father, but stayed in Rome from 1756 to 1760, where he was impressed by Piranesi; some drawings based on the latter's ‘Carceri d'invenzione’ show this influence. Back in Italy he earned his living in Paris, later in London, with making topographical prints; in the sixties he organized a number of exhibitions of his own work at the Society of Artists and the Free Society. In those days he also became involved in the building activities of Richard Grenville at the latters estate Stowe, where a few unexecuted designs are reminiscent of this, for instance of a new garden façade and a mausoleum for the owner.After having stayed in Amsterdam for a short period in 1762, he settled in the Dutch Republic once again by the end of 1773. With no less than three - unpreserved - designs he competed for the famous Groningen Town Hall competition of 1774, but he failed to win any prize: the opinion of the well-known physician Petrus Camper, who actually formed the jury on his own, was rather negative. Blondel, on the other hand, had a high opinion of himself, as was already evident before, and when he finally returned to France in 1777, he took pride in his contacts and merits in a letter to the Minister of War. In Paris, however, he had been forgotten, and later he disappeared in anonymity once again.Only in the early years of the French Revolution did he make himself heard, when he launched various plans to improve hygiene in Paris, and also accused a colleague of plagiarism by claiming the copyright of the latter's triumphal arch and altar for the fatherland, erected in 1790 on the occasion of the first commemoration of Quatorze Juillet.